(untitled) (International Journal of Environmental Sciences, 2025)
This experiment was carried out in shade of Department of Biology – Al-Rasheed University College for seasons 2019 and 2020 on mango seeds of Bull's Heart cultivar Three factors are used in this experiment, which are as follows: First: seed age factor, which includes one day after harvest (D1), two days after harvest (D2), and three days after harvest (D3). Second: growing medium factor (M), which includes loamy soil: peat moss (3:1) M1, loamy soil: peat moss (1:1) M2, and loamy soil: peat moss (1:3) M3. Third: humic acid addition factor, which includes adding 5 g.L-1 (H5) and adding 10 g.L-1 (H10). A factorial experiment was conducted within (RCBD) with five replicates for germination percentage (two seeds per experimental unit) and 3 replicates for vegetative traits (two seedlings per experimental unit). Thus, number of seeds planted in pots included in experiment was 180 seeds, and number of seedlings on which vegetative traits were studied was 108. Results showed that (D1M2H10) treatment gave the highest percentage of germination of 85.00 and 95.00 %, 123.15 and 158.64 cm as plant height ,13.04 and 13.88 mm as stem diameter, 71.00 and 83.33 leaf.seedling-1 as leaf number , 92.76 and 98.75 cm2 as leaf area, 30.18 and 32.96 mg.g-1 as leaves chlorophyll content , 0.425 and 0.449 % as leaves phosphor content and 1.928 and 2.108 % as leaves potassium content for two seasons, respectively